Ethanol induces locomotor activating effects in preweanling Sprague-Dawley rats - Arias, Carlos (2009)
Abuse of drugs exerts biphasic motor activity effects, which seem to be associated with their motivational effects. In the case of ethanol, heterogenous rat strains appear to be particularly sensitive to the sedative effects of the drug. In contrast, ethanol's activating effects have been consistently reported in rats genetically selected for ethanol affinity. Heightened ethanol affinity and sensitivity to ethanol's reinforcement are also observed in nonselected rats during early ontogeny. In the present study, we examined psychomotor effects of ethanol (1.25 and 2.5 g/kg) in 8-, 12-, and 15-day-old pups. Motor activity in a novel environment was assessed 5-10 or 15-20 min following drug treatment. Rectal temperatures and latency to exhibit the righting reflex were recorded immediately after locomotor activity assessment. Ethanol exerted clear activating effects at 8 and 12 days of age (Experiments 1a and 1b) and to a lesser extent at 15 days. At this age, ethanol enhanced locomotor activity in the first testing interval (Experiment 1b) and suppressed locomotion at 15-20 min (Experiment 1a). Ethanol-mediated motor impairment was more pronounced in the youngest group (postnatal day 8) than in the older ones. Blood ethanol concentrations were equivalent in all age groups. The present study indicates that preweanling rats are sensitive to ethanol's stimulating effects during the second postnatal week, and suggest that specific periods during early ontogeny of the rat can provide a valuable framework for the study of mechanisms underlying ethanol's stimulation and reinforcement effects. © 2009 Elsevier Inc. All rights reserved.